PENGARUH PENDEKATAN INKUIRI TERBIMBING TERHADAP PENGUASAAN KONSEP SISWA SD - Yasirli Amrina; Mai Sri Lena (Universitas Negeri Medan, 2021)
Abstract: The Effect Of The Guided Inquiry Approach On The Mastery Of Concepts In Elementary School Student. Knowing the influence of guided inquiry approaches to mastery of grade IV students' concepts in theme 7 learning at SDN 26 Painan Selatan is the purpose of the research. Quasi-Experimental quantitative type that uses Nonequivalent Control Group Design. The research sample was IVA class (control group) number of students 20 people and class IVB (experimental group) number of students 12 people. The instrument used is a multiple choice form test. Test t-test as a data analysis technique. The result of the study is that there are differences between the two groups. known from the value of thit more than tt which is 2.89 > 2.04; so Ha: μ1 ≠ μ2, meaning there is a significant difference between the mastery of the concept of experimental group students and the accepted control group. It was concluded that the use of guided inquiry approaches in the 7th theme learning had an effect on the mastery of the concept of grade IV students at SDN 26 South Painan. Keywords: Guided Inquiry Approach, Concept Mastery. Abstrak : Pengaruh Pendekatan Inkuiri Terbimbing Terhadap Penguasaan Konsep Siswa SD. Mengetahui pengaruh pendekatan inkuiri terbimbing terhadap penguasaan konsep siswa kelas IV pada pembelajaran tema 7 di SDN 26 Painan Selatan merupakan tujuan dari penelitian. Jenis kuantitatif berbentuk Quasi-Experimental yang menggunakan Nonequivalent Control Group Design . Sampel penelitian yaitu kelas IVA (kelompok kontrol) jumlah siswa 20 orang dan kelas IVB (kelompok eksperimen) jumlah siswa 12 orang. Instrumen yang digunakan adalah tes bentuk pilihan ganda. Uji t-test sebagai teknik analisis data. Hasil penelitian yaitu terdapat perbedaan antara kedua kelompok. diketahui dari nilai thit lebih dari tt yaitu 2,89 > 2,04; sehingga Ha: µ1 ≠ µ2, artinya ada perbedaan signifikan antara penguasaan konsep siswa kelompok eksperimen dengan kelompok kontrol diterima. Disimpulkan bahwa penggunaan pendekatan inkuiri terbimbing pada pembelajaran tema 7 berpengaruh terhadap penguasaan konsep siswa kelas IV di SDN 26 Painan Selatan. Kata Kunci : Pendekatan Inkuiri Terbimbing, Penguasaan Konsep.